2021
DOI: 10.1371/journal.ppat.1009841
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of mitochondrial biogenesis by virus infection triggers antiviral responses by cyclic GMP-AMP synthase

Abstract: In general, in mammalian cells, cytosolic DNA viruses are sensed by cyclic GMP-AMP synthase (cGAS), and RNA viruses are recognized by retinoic acid-inducible gene I (RIG-I)-like receptors, triggering a series of downstream innate antiviral signaling steps in the host. We previously reported that measles virus (MeV), which possesses an RNA genome, induces rapid antiviral responses, followed by comprehensive downregulation of host gene expression in epithelial cells. Interestingly, gene ontology analysis indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 57 publications
4
31
1
Order By: Relevance
“…[76][77][78] Similarly, researchers revealed that plasmid DNA transfection activates the cGAS-STING pathway, preparing the cells to be in an antiviral state that compromises the infectivity of coxsackievirus B3 (CVB3). 79 The cGAS-STING pathway also robustly evokes IFN response and effectively inhibits infection of several other RNA viruses, including chikungunya virus (CHIKV), 80,81 encephalomyocarditis virus (EMCV), 68,71 hepatitis C virus (HCV), 82 influenza A virus (IAV), 71,83 measles virus (MeV), 84,85 murine norovirus (MNV), 86,87 Nipah virus (NiV), 84 and Zika virus (ZIKV). 88 Surprisingly, in addition to antiviral role, STING has been discovered to be proviral in rare cases of RNA viral infections.…”
Section: Role Of Cgas-sting Pathway In Rna Viral Replicationmentioning
confidence: 99%
See 1 more Smart Citation
“…[76][77][78] Similarly, researchers revealed that plasmid DNA transfection activates the cGAS-STING pathway, preparing the cells to be in an antiviral state that compromises the infectivity of coxsackievirus B3 (CVB3). 79 The cGAS-STING pathway also robustly evokes IFN response and effectively inhibits infection of several other RNA viruses, including chikungunya virus (CHIKV), 80,81 encephalomyocarditis virus (EMCV), 68,71 hepatitis C virus (HCV), 82 influenza A virus (IAV), 71,83 measles virus (MeV), 84,85 murine norovirus (MNV), 86,87 Nipah virus (NiV), 84 and Zika virus (ZIKV). 88 Surprisingly, in addition to antiviral role, STING has been discovered to be proviral in rare cases of RNA viral infections.…”
Section: Role Of Cgas-sting Pathway In Rna Viral Replicationmentioning
confidence: 99%
“…71 A number of studies have reported that RNA viral infection can induce mtDNA leakage, consequently prompting the activation of the cGAS-STING axis. For example, infection with CHIKV, 81 DENV, 64,65 IAV, 71 MeV, 85 and MNV 86 EMCV infection, respectively, in a mitochondrial antiviral signalling (MAVS)-dependent manner. 71 (Figure 2).…”
Section: Mechanisms By Which Rna Viruses Activate the Cgas-sting Pathwaymentioning
confidence: 99%
“…RNA viruses such as measles virus, which do not possess cGAS ligands, induce mtDNA-dependent cGAS activation in addition to activating RNA sensing pathways. 84 During intrinsic apoptosis, Bax/Bak-mediated mitochondrial outer membrane permeabilization (MOMP) triggers the cytosolic release of mtDNA that activates cGAS and STING, which is inhibited by apoptotic caspases (caspase-9 and caspase-3/7) that are downstream of MOMP. 85,86 The mechanism by which these caspases inhibit cGAS-STING activation is likely via the cleavage of cGAS, as described later.…”
Section: Self-dna As An Ifn-inducing Cgas Substratementioning
confidence: 99%
“…The perturbation of mitochondrial function either by infectious or non‐infectious stimuli leads to mitochondrial damage that releases mtDNA into the cytosol. RNA viruses such as measles virus, which do not possess cGAS ligands, induce mtDNA‐dependent cGAS activation in addition to activating RNA sensing pathways 84 . During intrinsic apoptosis, Bax/Bak‐mediated mitochondrial outer membrane permeabilization (MOMP) triggers the cytosolic release of mtDNA that activates cGAS and STING, which is inhibited by apoptotic caspases (caspase‐9 and caspase‐3/7) that are downstream of MOMP 85,86 .…”
Section: Sources Of Substrate Dna That Activate Cgas‐sting Signalingmentioning
confidence: 99%
“…inflammatory signals acting on mitochondrial physiology—has been described in this axis. In epithelial cell infections with measles virus (MeV), a negative-sense single-stranded RNA (-ssRNA) virus, recent findings showed that mitochondrial biogenesis is downregulated and mitochondrial elongation can be observed [ 108 ]. In addition, the release of mtDNA into the cytosol has been detected, and activation of the cGAS/STING axis led to an antiviral response.…”
Section: Mitochondria and Infectionmentioning
confidence: 99%